Effect of the nano-titanium dioxide (nano-TiO2) coating on the photoaging properties of thermally treated bamboo. Issue 6 (2nd November 2022) - Tang, Ao'ran; Huang, Yaqian; Zhang, Wen; Yu, Ying; Yang, Yong; Yuan, Zhurun; Wang, Xinzhou
ABSTRACT: Moso bamboo was firstly treated in a vacuum chamber at 150°C, 170°C, 190°C, and 210°C for 1, 2, and 3 h, respectively. Nano-TiO2 gel were then coated on the surface of thermally treated (TM) bamboo. Finally, specimens were radiated by an accelerated aging chamber of xenon lamp for 144 h. Chroma Meter, Scanning electron microscopy and Energy-dispersive spectroscopy (SEM-EDS) were applied to investigate the effect of nano-TiO2 coating on the surface color stability of TM bamboo. Results revealed that TM imposed a significant effect on the surface color of bamboo, e.g. when treatment temperature and duration increased, bamboo surface became darker. The color parameters of TM bamboo coated with nano-TiO2 gel after aging were close to the bamboo before aging, indicating that the photo-discoloration resistance of the TM bamboo has been improved. The nano-TiO2 gel with a concentration of 10% shows a better effect than that of 5%. After aging for 144 h, the Δ E of TM bamboo (190°C/2 h) coated by nano-TiO2 gel with a concentration of 10% was 2.90, which decreases by 25% compared with that of uncoated bamboo. Furthermore, the nano-TiO2 coating had no obvious aging failure after 144 h aging, which avoided the leaching of TiO2 particles during the long-term service.